(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
At the present time, great attention is being paid to the development of chicken farming in our republic. It can be solved by developing ways to reduce the cost of food ration, using secondary products of the food industry. Waste from food industry enterprises is an important source of replenishment of food reserves. Silkworm waste is included in the above components to obtain productivity-enhancing substances. These include chitosan, which is derived from chitin by deacetylation to varying degrees. One of the foods is whey powder. Whey milk protein has a set of essential amino acids for poultry. Compared to the currently used industrial and vivarium feeds, the results of this product have a high level of efficiency.